Effect of Operating Cconditions on Hydrodesulfurization of Vacuum Gas Oil - A. Karim Mohammed, Abdul Halim; A.KARIM, Abdul Mun’m; A.Areff, Haider (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
This study was conducted according to contract with the North Refineries Company-Baiji and deals with the hydrodesulphurization of vacuum gas oil of Kirkuk crude oil, boiling range 611-833 K. A trickle bed reactor packed with a commercial cobalt-molybdenum on alumina catalyst was used. The operating conditions were: temperature range 583-643 K, liquid hourly space velocity range 1.50-3.75 1/h, hydrogen to oil ratio about 250 l/l and pressure kept constant at 3.5MPa. The results showed that the aromatic content decreased and sulfur removal increased with increasing temperature and decreasing space velocity. The properties (viscosity, density, flash point and carbon residue) of the products decrease with temperature increasing, but the aniline point increased.